From highlight to insight, the role of visual input enhancement in vocabulary Mastery with Kahoot - Fatmawati Fatmawati; Aminah Suriaman; Mukrim Mukrim (Publikasi Indonesia, 2024)
This research aims at solving the problem of low vocabulary mastery encountered by the class eight students of SMP Negeri 3 Banawa. The use of Kahoot, assisted by input enhancement techniques, was used to address this problem by attempting to increase vocabulary mastery of the students through a two-cycle Classroom Action Research (CAR) design, consisting of planning, acting, observing, and reflecting. The first cycle consisting of three meetings employed Kahoot, assisted by input enhancement technique with bolded, underlined modified texts, and the second cycle consisting of three meetings utilized Kahoot, assisted by input enhancement with highlighted, enlarged fonts of modified texts. Quantitative data from post-tests and qualitative data from field notes, observation sheets, interviews, and questionnaires were collected to evaluate student progress and engagement throughout the study. The criteria of success applied in this research is 75 or 70 % of the students achieved the passing grade. Result of post-test in the first cycle showed that only 23 % of the students achieved the passing grade. The data from observation and fieldnotes supported the finding that the plans needed to be revised, input manipulation changed and students were grouped. Findings from the intervention in the second cycle denotes that 73% of students achieving the passing grade (KKM) in vocabulary mastery. It means that the criteria of success were fulfilled. In addition, findings from qualitative data indicated the enhancement of student engagement, interaction, motivation, attention, and vocabulary retention. The research highlights the potential of Kahoot assisted by visual input enhancement techniques as a good teaching media to be utilized by teachers in increasing vocabulary mastery of EFL learners.